Comprehensive Review of Health Workers’ Roles in Mental Health Management in Hospitals - lajam, Yahay Ahamad; alzogly, Abdhudi Ahmad Ali; Alqahtani, Basim Abdullah Abdullah; Saleh, Dafer Ahmad Saleh AL; Alshahy, Majed Hamad Mahdi; Albahri, Ali Dahfer; Alkorbi, Mobarak Abdullah Salmen; Alsaiari, Ali Ayed Salmen; Alqarni, Esraa Hosain; Mashnafi, Salma Ateya (Journal of Ecohumanism, 2024)
The following research paper seeks to review health workers' functions in mental health management in hospitals. More generally, social workers review the roles of the multidisciplinary teams involved in mental health, factors inhibiting effective care, and prospects for enhancing mental health delivery. This research focuses on a literature review where quantitative and qualitative data draw attention to prevalent trends and practices. The recommendations propose improving health worker training and allocating efficient solutions for better mental health management.